Potent β-lactam-based tyrosyl-DNA phosphodiesterase 1 inhibitors identified by a virtual screen - Xue Zhi Zhao; Wenjie Wang; Kiall F. Suazo; Md Rasel Al Mahmud; Keli Agama; George T. Lountos; Thorkell Andresson; Yves Pommier; Terrence R. Burke (Scientific Reports)
Abstract Tyrosyl-DNA phosphodiesterase 1 (TDP1) is an important therapeutic target. We recently reported several crystal structures of TDP1 with small molecules bound within the catalytic pocket. These molecules bind by forming hydrogen bonds with residues of the catalytic HKN motifs. Guided by these interactions, in our current work, we used the MolSoft ICM Pro suite of software to perform a virtual screen of the publicly available DrugBank 5.0 (3449 structures) for the ability to bind to the TDP1 catalytic pocket. Among compounds identified as giving good binding scores were several β-lactams. The β-lactam pharmacophore serves as a key component in a range of antibiotics. We subjected a subset of the β-lactam hits to gel-based TDP1 fluorescence catalytic assays and established that certain members showed micromolar TDP1 inhibition. In follow-up, we evaluated a commercially available library of 90 β-lactam antibiotics. This led to our identification of additional β-lactams having micromolar TDP1 inhibitory potencies. In particular, cephalosporin C showed single-digit micromolar TDP1 IC50 values. Since β-lactams can form covalent bonds with serine residues in target penicillin-binding proteins (PBPs), we performed docking studies with cephalosporin C, which showed that it bound within the catalytic pocket and extended into the DNA substrate binding channel. Importantly, the modeling indicated that both noncovalent and covalent binding modes were theoretically possible. Surface plasmon resonance analysis demonstrated its non-covalent binding mode. Thus, β-lactams may serve as a new and potentially useful platform to design TDP1-binding ligands that interact with the catalytic pocket and extend into the DNA substrate binding channel.